KARAKTERISASI PRODUK GEN PENGKODE CHAPERONE BACILLUS SP. RP1 - Kumaunang, Maureen; Mandik, Yohanis (CHEMISTRY PROGRESS, 2010)
Molecular chaperone is the group of protein that assist in the correct folding or assembly of other proteins invivo. The objective of this research was to characterize the product of gene encoding chaperone from Bacillussp. RP1 by using in-silico analysis. Analysis of 1053 bp from DNA fragment isolated by PCR showed that it has97% similarity with putative chaperone of Geobacillus kaustophilus (BA000043.1) and 86% similarity with DnaKoperon of B. stearothermophilus (X90709.1). Structure prediction of DnaJ Bacillus sp. RP1 showed that it hassimilar J-domain with that of DnaJ Escherichia coli but cys-rich domain is different.